Chiral quaternary phosphonium salts: a new class of organocatalysts - Enders, D.; Nguyen, Thanh Vinh (The Royal Society of Chemistry, 2012)
Phase-transfer catalysis has widely been used as a prime synthetic tool for both laboratory and industrial processes. During the last twenty years, asymmetric phase-transfer catalysis using chiral organocatalysts has attracted widespread interest. However, the scope of chiral phase-transfer catalysis has been limited mostly to the quaternary ammonium salts. As an emerging area, the recent developments in the application of quaternary phosphonium salts as chiral phase-transfer catalysts are discussed in this article.